Low smoke, flame retardant polyvinyl chloride composition, method of making and use in security cables

CN122917465APending Publication Date: 2026-10-16HANGZHOU LINAN GUANGDA CABLE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611419587.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-14
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,该体系存在无法回避的矛盾:大量三氯化锑离开火焰区后氧化成固体微粒,构成浓密白烟

Benefits of technology

本申请中通过聚氯乙烯树脂、偏苯三酸三辛酯、聚合型含磷聚酯增塑剂、钙锌复合热稳定剂、分级包覆型阻燃抑烟协效剂、三氧化二锑和氯化石蜡-70等组分的配合,形成兼具气相阻燃、凝聚相成炭及无机屏障作用的低烟阻燃体系;在减少三氧化二锑用量的同时保持较高阻燃效率,并降低烟密度和热释放速率;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application relates to the technical field of high-molecular flame-retardant materials, and particularly discloses a low-smoke flame-retardant polyvinyl chloride composition, a preparation method and application of the low-smoke flame-retardant polyvinyl chloride composition in security and protection cables. The low-smoke flame-retardant polyvinyl chloride composition is prepared from the following components in parts by weight: 100 parts of polyvinyl chloride resin, 25-40 parts of trioctyl trimellitate, 6-15 parts of a polymeric phosphorus-containing polyester plasticizer, 3-6 parts of a calcium-zinc composite heat stabilizer, 14-24 parts of a hierarchical coated flame-retardant smoke-suppressing synergist, 1.5-3.5 parts of antimony trioxide, 1-4 parts of chlorinated paraffin-70, 0.5-2 parts of an acrylate processing aid, 0.3-0.6 parts of a lubricant and 0.2-0.8 parts of an antioxidant. The polyvinyl chloride composition has both flame-retardant and smoke-suppressing properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the technical field of polymer flame-retardant materials, and in particular to a low-smoke flame-retardant polyvinyl chloride composition, its preparation method, and its application in security cables. Background Technology

[0002] Flexible polyvinyl chloride (PVC) is highly flammable due to the addition of large amounts of plasticizers, necessitating flame-retardant treatment. Currently, the most mature flame-retardant system is a gas-phase flame-retardant system composed of antimony trioxide and halogen donors. Its flame-retardant mechanism involves the generation of antimony trichloride during combustion, which efficiently captures free radicals in the gas phase, halting the chain reaction. However, this system suffers from an unavoidable contradiction: a large amount of antimony trichloride oxidizes into solid particles after leaving the flame zone, forming dense white smoke. To address the smoke problem, the industry has attempted to add smoke suppressants such as molybdenum, iron, and tin. While these substances can reduce smoke precursors by promoting char formation in the condensed phase, they consume some hydrogen chloride, thus interfering with the gas-phase flame-retardant efficiency of antimony trichloride and leading to a decrease in the oxygen index. Therefore, a sharp conflict exists between "flame retardancy" and "smoke suppression." Conventional physical blending cannot simultaneously achieve ideal levels of both properties. Thus, there is an urgent need to obtain a PVC material that balances both flame-retardant and smoke-suppressive properties. Summary of the Invention

[0003] In order to obtain a polyvinyl chloride material that combines flame retardancy and smoke suppression properties, this application provides a low-smoke flame-retardant polyvinyl chloride composition, a preparation method, and its application in security cables.

[0004] Firstly, this application provides a low-smoke flame-retardant polyvinyl chloride composition, which adopts the following technical solution: A low-smoke flame-retardant polyvinyl chloride (PVC) composition, wherein the raw materials of the low-smoke flame-retardant PVC composition include the following components in parts by weight: 100 parts of PVC resin, 25-40 parts of trioctyl trimellitate, 6-15 parts of polymeric phosphorus-containing polyester plasticizer, 3-6 parts of calcium-zinc composite heat stabilizer, 14-24 parts of graded coating flame-retardant and smoke-suppressing synergist, 1.5-3.5 parts of antimony trioxide, 1-4 parts of chlorinated paraffin-70, 0.5-2 parts of acrylate processing aid, 0.3-0.6 parts of lubricant, and 0.2-0.8 parts of antioxidant; the graded coating flame-retardant and smoke-suppressing synergist includes a sheet-like sericite skeleton, a zinc hydroxystannate-zinc borate composite loading layer loaded on the surface of the sheet-like sericite skeleton, a zinc phytate coordination layer bonded to the surface of the zinc hydroxystannate-zinc borate composite loading layer, and an epoxy-based polysiloxane protective layer coating the outside of the zinc phytate coordination layer.

[0005] By adopting the above technical solution, trioctyl trimellitate imparts good flexibility, heat resistance and migration resistance to the composition; while playing a plasticizing role, the polymeric phosphorus-containing polyester plasticizer can also provide phosphorus source and organic carbon source during combustion, promote the further cyclization, cross-linking and carbonization of the conjugated segments formed after PVC dehydrochlorination, and is not easy to migrate out of the PVC matrix, which is conducive to maintaining the flame retardant performance and mechanical properties of the cable during long-term use. Antimony trioxide reacts with PVC and chlorinated paraffin-70 to form a gaseous free radical capture system in the early stage of combustion, which quickly inhibits the flame chain reaction. Furthermore, controlling the antimony trioxide content to 1.5–3.5 parts can reduce the risk of forming a large number of antimony-containing smoke particles in traditional high-antimony flame retardant systems. In the graded coating type flame retardant and smoke suppressant synergist, zinc hydroxystannate promotes the transformation of PVC thermal degradation products into condensed phase and reduces the amount of smoke precursors generated; zinc borate forms a boron-containing glassy substance upon heating, which can seal the pores of the char layer and improve the integrity of the char layer; flaky sericite provides a two-dimensional inorganic framework, extending the transfer path of heat, oxygen and volatile pyrolysis products; zinc phytate and polymeric phosphorus-containing polyester plasticizer together form a phosphorus-zinc synergistic char-forming system; epoxy-based polysiloxane improves the interfacial compatibility between inorganic flame retardant particles and PVC matrix, and forms a silicon-containing inorganic phase after combustion; thus, a composite flame retardant mechanism of "antimony-chlorine gas phase flame retardancy, phosphorus-tin-zinc catalytic char formation, and boron-silicon-aluminum inorganic barrier" is formed, which maintains high flame retardant efficiency while reducing the amount of antimony trioxide used, and reduces smoke density and heat release rate.

[0006] In one specific implementation scheme, the preparation method of the graded coated flame retardant and smoke suppressant synergist includes the following steps: Preparation of primary coating slurry: Flake sericite is added to a mixed dispersion medium of water and ethanol and dispersed at 800-1500 rpm for 20-40 min to obtain a flake sericite dispersion; zinc hydroxystannate and zinc borate are added to the flake sericite dispersion and sheared and dispersed at 1200-2000 rpm for 30-60 min, followed by wet milling to load the zinc hydroxystannate and zinc borate onto the surface of the flake sericite, forming a zinc hydroxystannate-zinc borate composite loading layer, thus obtaining a primary coating slurry; Preparation of secondary coating slurry: Zinc phytate is added to the primary coating slurry, the pH value of the system is adjusted to 5.5-7.0, and the mixture is stirred at 50-70℃ for 0.5-2 hours, so that the zinc phytate is bonded to the surface of the zinc hydroxystannate-zinc borate composite loading layer through coordination and hydrogen bonding to form a zinc phytate coordination layer, thus obtaining the secondary coating slurry; Preparation of epoxy polysiloxane protective layer: Epoxy polysiloxane is added to the secondary coating slurry and stirred at 70-90°C for 1-3 hours to coat the outer side of the zinc phytate coordination layer with epoxy polysiloxane, forming an epoxy polysiloxane protective layer; after filtration, washing, drying and pulverizing, a graded coating type flame retardant and smoke suppressant synergist is obtained; wherein the mass ratio of flaky sericite, zinc hydroxystannate, zinc borate, zinc phytate and epoxy polysiloxane is (10-18):(45-55):(25-35):(3-7):(2-4).

[0007] By adopting the above technical solution, in the preparation of the coating slurry, the water-ethanol mixed medium can take into account both the dispersibility of flaky sericite and the wettability of inorganic powders. After high-speed shearing and wet grinding, zinc hydroxystannate and zinc borate can be uniformly loaded on the surface of flaky sericite, avoiding the problems of agglomeration and spatial separation that occur when zinc hydroxystannate, zinc borate and sericite are directly added to PVC. The zinc hydroxystannate-zinc borate composite loading layer concentrates the catalytic char-forming component and the glassy sealing component on the same flaky framework surface, so that the char layer promoted by zinc hydroxystannate can be sealed by the glassy substance formed by zinc borate in time, thereby reducing the through-pores in the char layer. The zinc phytate coordination layer can coordinate and bind or hydrogen bond with the metal active sites on the surface of zinc hydroxystannate and zinc borate, so that the phosphorus source and the tin and zinc catalytic sites maintain a short interaction distance. During combustion, the phosphoric acid structure formed by zinc phytate can promote the char formation of PVC conjugated segments, and the tin and zinc active sites further catalyze cross-linking and aromatization, thereby improving the char formation efficiency of the condensed phase.

[0008] In one specific implementation, the method for preparing the polymeric phosphorus-containing polyester plasticizer includes the following steps: Esterification reaction: Adipic acid, sebacic acid, 1,4-butanediol, neopentyl glycol and 2-carboxyethylphenylphosphonic acid are mixed, tetrabutyl titanate is added, and the mixture is heated to 150-180℃ under nitrogen protection to carry out the esterification reaction until the acid value of the reaction system is reduced to below 15mgKOH / g. Polycondensation reaction: The reactants obtained from the esterification reaction step are heated to 190-220°C, and the absolute pressure of the reaction system is reduced to 0.5-5 kPa, and the polycondensation reaction is carried out for 1-4 hours; End-capping reaction: 2-ethylhexanol is added to the polycondensation product obtained in the polycondensation reaction step for end-capping reaction. The amount of 2-ethylhexanol is 1-5% of the mass of the obtained polycondensation product. The reaction is carried out at 170-200℃ for 0.5-2h to obtain the polymeric phosphorus-containing polyester plasticizer. The mass ratio of adipic acid, sebacic acid, 1,4-butanediol, neopentyl glycol and 2-carboxyethylphenylphosphonic acid is (32-38):(14-18):(20-24):(11-15):(12-16). The amount of tetrabutyl titanate is 0.05-0.12% of the total mass of the five raw materials.

[0009] By adopting the above technical solutions, adipic acid provides suitable flexible aliphatic segments, which is beneficial to improving the flexibility of PVC; sebacic acid has long methylene segments, which can improve the low-temperature flexibility and hydrophobicity of plasticizers; neopentyl glycol has a branched structure, which is beneficial to improving the hydrolysis resistance and heat resistance of polyester; 1,4-butanediol is beneficial to controlling the flexibility of polyester segments and plasticizing efficiency; 2-carboxyethylphenylphosphine enters the polyester backbone in the form of a reactive phosphorus-containing monomer, making it difficult for phosphorus to migrate or precipitate, and forming phosphoric acid or polyphosphoric acid structures during combustion, promoting the cross-linking of conjugated segments after dehydrochlorination of PVC into carbon; this polymeric phosphorus-containing polyester plasticizer forms a synergistic effect with zinc phytate and zinc hydroxystannate: the phosphorus-containing polyester provides a continuously distributed phosphorus source and carbon source, zinc phytate provides polyphosphate sites, and zinc hydroxystannate provides metal catalytic sites, thereby forming a phosphorus-tin-zinc synergistic carbonization system.

[0010] In one specific embodiment, the raw materials of the low-smoke flame-retardant polyvinyl chloride composition further include 1.5 to 4 parts by weight of piperazine pyrophosphate and 0.5 to 2 parts by weight of melamine cyanurate.

[0011] By adopting the above technical solution, piperazine pyrophosphate, upon heating, generates a phosphoric acid structure, which can promote the dehydration, cyclization, aromatization, and cross-linking of the conjugated segments formed after PVC dehydrochlorination to form char. Its piperazine structure can also provide a certain nitrogen source for the char layer, improving its stability. Melamine cyanurate, upon thermal decomposition, can absorb some heat and release non-flammable gases such as ammonia and nitrogen. These released gases can dilute flammable thermal decomposition products and moderately expand the viscous char layer formed by phosphorus-based charring, creating a porous, expanded char layer with heat insulation and oxygen barrier properties. The combination of piperazine pyrophosphate, melamine cyanurate, and polymeric phosphorus-containing polyester plasticizer... Polymerized phosphorus-containing polyester plasticizers provide a compatible organic carbon source and some phosphorus source; piperazine pyrophosphate provides an acid source, promoting rapid dehydration and cross-linking of the carbon source; melamine cyanurate provides a gas source, causing the formed char layer to expand; the three constitute a complete "carbon source-acid source-gas source" intumescent flame retardant system. At the same time, the intumescent char layer can also combine with the inorganic components of the flaky sericite, zinc borate, and epoxy polysiloxane in the graded coating flame retardant and smoke suppressant synergist after combustion, forming a structure in which the intumescent char layer and the inorganic barrier support each other, reducing char layer shrinkage and cracking. Therefore, it can further reduce the heat release rate and total smoke release, and improve the problem of thin char layer and insufficient thermal shock resistance of the pure inorganic flame retardant system.

[0012] In one specific implementation, the raw materials of the low-smoke flame-retardant polyvinyl chloride composition further include 0.4 to 1.5 parts by weight of zinc molybdate and 0.8 to 3 parts by weight of boehmite.

[0013] By adopting the above technical solution, antimony trioxide mainly plays a gas-phase flame-retardant role, but after combustion, it may form antimony-containing particles and increase smoke density. Zinc molybdate can promote the transformation of aromatic smoke precursors and unsaturated fragments generated by PVC pyrolysis into the condensed phase, fixing more carbon in the char residue, thereby reducing the proportion of smoke precursors entering the gas phase. Therefore, zinc molybdate can compensate for the defect of the antimony trioxide system, which has "high flame-retardant efficiency but easily increases smoke density," improving smoke suppression performance while maintaining early gas-phase flame-retardant efficiency. Zinc molybdate can also work synergistically with graded coated flame-retardant and smoke-suppressant agents. Zinc hydroxystannate forms a molybdenum-tin-zinc multimetallic catalytic system, which can promote the further cyclization and aromatization of the conjugated polyolefin segments formed after PVC dehydrochlorination, improve the char yield, and reduce the smoke particles generated by incomplete combustion. Boehmite dehydrates and absorbs heat during heating, and the released water vapor can dilute the combustible gases in the combustion zone. After heating, it forms an alumina phase, which can combine with the boron-containing glass phase formed by zinc borate and the silicon-containing inorganic phase formed by epoxy polysiloxane to form an aluminum-boron-silicon composite ceramic barrier, further improving the flame retardant stability and smoke suppression effect.

[0014] Secondly, this application provides a method for preparing a low-smoke flame-retardant polyvinyl chloride composition, which adopts the following technical solution: A method for preparing a low-smoke flame-retardant polyvinyl chloride composition includes the following steps: Preparation of flame retardant masterbatch: The graded coating flame retardant and smoke suppressant synergist, antimony trioxide, chlorinated paraffin-70, part of trioctyl trimellitate and part of polymeric phosphorus-containing polyester plasticizer are mixed and milled to obtain flame retardant masterbatch. Premix preparation: Polyvinyl chloride resin, remaining trioctyl trimellitate, polymeric phosphorus-containing polyester plasticizer, calcium-zinc composite heat stabilizer, acrylate processing aids and antioxidants are added to a high-speed mixer and mixed. When the temperature of the mixture reaches 90-110℃, flame retardant masterbatch and lubricant are added. Mixing is continued until 115-125℃ before discharge to obtain the premix. Extrusion granulation: The premixed material is added to a twin-screw extruder and plasticized, extruded and granulated at 145-165°C to obtain a low-smoke flame-retardant polyvinyl chloride composition.

[0015] By adopting the above technical solution, using the process of flame retardant masterbatch preparation, high-speed premixing, and twin-screw extrusion granulation, multiple flame retardant and smoke-suppressing components are uniformly dispersed in the PVC matrix. Twin-screw extrusion granulation can further achieve dispersion, plasticization, and homogenization, so that the flame retardant and smoke-suppressing components are uniformly distributed in the final granules, thereby improving the performance of the low-smoke flame retardant PVC composition.

[0016] In one specific implementation scheme, when the raw materials of the low-smoke flame-retardant polyvinyl chloride composition further include piperazine pyrophosphate, melamine cyanurate, zinc molybdate, and boehmite, the preparation steps of the flame-retardant masterbatch are as follows: mixing and milling a graded coating flame-retardant and smoke-suppressing synergist, antimony trioxide, chlorinated paraffin-70, a portion of trioctyl trimellitate, a portion of polymeric phosphorus-containing polyester plasticizer, piperazine pyrophosphate, melamine cyanurate, zinc molybdate, and boehmite to obtain the flame-retardant masterbatch.

[0017] By adopting the above technical solution, piperazine pyrophosphate, melamine cyanurate, zinc molybdate, and boehmite are first prepared together with the basic flame retardant components to form a flame retardant masterbatch. The wetting effect of the plasticizer is used to improve the dispersion uniformity of the four new powders in PVC, which can shorten the spatial distance between different synergistic components and improve the efficiency of simultaneous activation of multiple flame retardant mechanisms.

[0018] In one specific implementation, in the extrusion granulation step, the twin-screw extruder is sequentially configured with a first plasticizing zone, a second plasticizing zone, a third plasticizing zone, a vacuum exhaust zone, and a metering zone along the material conveying direction; the temperature of the first plasticizing zone is 145–150°C, the temperature of the second plasticizing zone is 150–155°C, the temperature of the third plasticizing zone is 155–160°C, the temperature of the vacuum exhaust zone is 155–162°C, and the temperature of the metering zone is 158–165°C; the vacuum degree of the vacuum exhaust zone is -0.06 to -0.09 MPa, the screw speed of the twin-screw extruder is 120–250 rpm, and the residence time of the material in the twin-screw extruder is 1.5–4 min.

[0019] By adopting the above technical solution, the temperature, vacuum degree, screw speed and residence time of each zone of the twin-screw extruder are further limited. This ensures that PVC is fully plasticized while reducing its risk of thermal decomposition. The temperature and residence time control also helps to protect the epoxy polysiloxane protective layer and prevent it from being damaged prematurely during the extrusion process. This allows the graded coating synergist to fully expose the active sites of tin, zinc and phosphorus during the combustion stage.

[0020] Thirdly, the security cable provided in this application adopts the following technical solution: A security cable includes a conductor, an insulation layer covering the outside of the conductor, and a sheath layer located outside the insulation layer; the sheath layer is made of the low-smoke flame-retardant polyvinyl chloride composition.

[0021] By adopting the above technical solution, the sheath layer formed by the low-smoke flame-retardant polyvinyl chloride composition can rapidly reduce the flame propagation speed in the early stage of a fire through the gas-phase flame-retardant effect of antimony trioxide and chlorinated paraffin-70. During continuous heating, the polymeric phosphorus-containing polyester plasticizer, zinc phytate, zinc hydroxystannate, and piperazine pyrophosphate promote the formation of a char layer. Melamine cyanurate causes the char layer to expand moderately. Zinc borate, sericite, polysiloxane, and boehmite further form an inorganic barrier.

[0022] In one specific implementation, the thickness of the sheath layer is 0.08-0.15 times the outer diameter of the security cable.

[0023] By adopting the above technical solution, the sheath thickness is controlled at 0.08 to 0.15 times the outer diameter of the cable, which allows the graded coating flame retardant and smoke suppressant synergist and the phosphorus-nitrogen expansion carbonization system to form a continuous carbon layer of sufficient thickness on the sheath surface, while maintaining the acceptable bending radius and construction performance of the cable.

[0024] In summary, this application includes at least one of the following beneficial technical effects: This application combines polyvinyl chloride resin, trioctyl trimellitate, polymeric phosphorus-containing polyester plasticizer, calcium-zinc composite heat stabilizer, graded coating flame retardant and smoke suppressant synergist, antimony trioxide, and chlorinated paraffin-70 to form a low-smoke flame retardant system that combines gas-phase flame retardancy, condensed-phase charring, and inorganic barrier effects; it maintains high flame retardant efficiency while reducing the amount of antimony trioxide used, and reduces smoke density and heat release rate. The method in this application utilizes a process of flame retardant masterbatch preparation, high-speed premixing, and twin-screw extrusion granulation to uniformly disperse multiple flame retardant and smoke-suppressing components in the PVC matrix. Twin-screw extrusion granulation can further achieve dispersion, plasticization, and homogenization, so that the flame retardant and smoke-suppressing components are uniformly distributed in the final granules, thereby improving the performance of the low-smoke flame retardant polyvinyl chloride composition. The security cable in this application uses this low-smoke flame-retardant polyvinyl chloride composition to form a sheath layer, which can rapidly reduce the flame propagation speed in the early stage of a fire through the gas-phase flame retardant effect of antimony trioxide and chlorinated paraffin-70; during continuous heating, polymeric phosphorus-containing polyester plasticizer, zinc phytate, zinc hydroxystannate and piperazine pyrophosphate promote the formation of a char layer; melamine cyanurate causes the char layer to expand moderately; zinc borate, sericite, polysiloxane and boehmite further form an inorganic barrier. Detailed Implementation

[0025] The present application will be further described in detail below with reference to the embodiments.

[0026] All raw materials used in the examples are commercially available. The flaky sericite has a D50 of 8 μm and an aspect ratio of 50–70; the PVC resin used is SG-5 type suspension PVC resin with an average degree of polymerization of 1000; the calcium-zinc composite heat stabilizer is BAEROPAN MC 90003 KA type calcium-zinc composite heat stabilizer for cable materials; the acrylate processing aid is PARALOID K-120ND type processing aid; the lubricant is AC 6A type low-density polyethylene homopolymer wax; the antioxidant is Irganox 1010; the piperazine pyrophosphate is industrial-grade ultrafine PAPP with a purity of 98.5 wt% and a D50 particle size of 5 μm; the melamine cyanurate is Melapur MC type melamine cyanurate with a D50 particle size of 4 μm; the zinc molybdate is high-purity zinc molybdate with a purity of 99.2 wt% and a D50 particle size of 0.8 μm; and the boehmite is ACTILOX. Type B60 boehmite has an alumina monohydrate content of 99 wt%, a D50 particle size of 0.7 μm, and a D90 particle size of 1.4 μm.

[0027] Preparation Example

[0028] Preparation Example 1 Preparation Example 1 provides a method for preparing a graded coated flame retardant and smoke suppressant synergist, comprising the following steps: Preparation of primary coating slurry: Deionized water and anhydrous ethanol were stirred at 600 rpm for 8 min to obtain a mixed dispersion medium. Flake sericite was added to the mixed dispersion medium of water and ethanol and dispersed at 1150 rpm for 30 min to obtain a flake sericite dispersion. Zinc hydroxystannate and zinc borate were added to the flake sericite dispersion at 32℃ and sheared at 1600 rpm for 45 min. Wet milling was then performed using 0.6 mm diameter zirconia grinding beads with a filling rate of 70%. The slurry circulation flow rate was 450 L / h, and the milling was repeated twice. The slurry temperature was 40℃, allowing zinc hydroxystannate and zinc borate to be loaded onto the surface of the flake sericite, forming a zinc hydroxystannate-zinc borate composite loading layer, thus obtaining the primary coating slurry. The weight ratio of flake sericite, deionized water, and anhydrous ethanol was 14:320:80. Preparation of secondary coating slurry: 5 kg of zinc phytate was added to a water-ethanol mixture with a mass ratio of zinc phytate, water, and ethanol of 5:20:5. The mixture was dispersed at 1250 rpm for 25 min to obtain a zinc phytate pre-dispersion. The phytate pre-dispersion was added to the primary coating slurry. The pH of the system was adjusted to 6.2 using a 5 wt% acetic acid aqueous solution or a 5 wt% ammonia solution. The mixture was stirred at 60 °C for 1.2 h to allow zinc phytate to bind to the surface of the zinc hydroxystannate-zinc borate composite loading layer through coordination and hydrogen bonding, forming a zinc phytate coordination layer, thus obtaining the secondary coating slurry. Preparation of epoxy-based polysiloxane protective layer: Epoxy-based polysiloxane was pre-diluted with ethanol at a weight ratio of 3:20. The mixture was stirred at 650 rpm for 15 min to obtain a diluted epoxy-based polysiloxane solution. This diluted solution was added to the secondary coating slurry, and the mixture was stirred at 80°C and 400 rpm for 2 h to coat the outer side of the zinc phytate coordination layer, forming an epoxy-based polysiloxane protective layer. After filtration and washing, the mixture was vacuum dried at 80°C for 10 h, pulverized, and passed through a 200-mesh sieve to obtain a graded coating type flame retardant and smoke suppressant synergist. The mass ratio of flaky sericite, zinc hydroxystannate, zinc borate, zinc phytate, and epoxy-based polysiloxane was 14:50:30:5:3.

[0029] Preparation Example 2 The difference between Preparation Example 2 and Preparation Example 1 is that the mass ratio of sheet sericite, zinc hydroxystannate, zinc borate, zinc phytate, and epoxy polysiloxane is 10:45:25:3:2; the remaining steps are the same as in Preparation Example 1.

[0030] Preparation Example 3 The difference between Preparation Example 3 and Preparation Example 1 is that the mass ratio of sheet sericite, zinc hydroxystannate, zinc borate, zinc phytate, and epoxy polysiloxane is 18:55:35:7:4; the remaining steps are the same as in Preparation Example 1.

[0031] Preparation Example 4 Preparation Example 4 provides a method for preparing a polymeric phosphorus-containing polyester plasticizer, comprising the following steps: Esterification reaction: Adipic acid, sebacic acid, 1,4-butanediol, neopentyl glycol, and 2-carboxyethylphenylphosphonic acid were mixed, and tetrabutyl titanate was added. Under nitrogen protection, the mixture was first kept at 150°C for 30 min, then the temperature was increased to 175°C over 75 min, and the esterification reaction was carried out at 175°C for 3 h until the acid value of the reaction system decreased to below 15 mg KOH / g. The mass ratio of adipic acid, sebacic acid, 1,4-butanediol, neopentyl glycol, and 2-carboxyethylphenylphosphonic acid was 35:16:22:13:14, and the amount of tetrabutyl titanate was 0.08% of the total mass of the five raw materials. Polycondensation reaction: The reactants obtained from the esterification reaction step were heated to 205°C and the absolute pressure of the reaction system was reduced to 1.9 kPa, and the polycondensation reaction was carried out for 2.5 h. End-capping reaction: 2-Ethylhexanol is added to the polycondensation product obtained in the polycondensation reaction step. The amount of 2-ethylhexanol is 3% of the mass of the obtained polycondensation product. The end-capping reaction is carried out at 185°C for 1.2 h. The reaction system is cooled to 140°C. Under nitrogen protection, the molten product is passed through a 120-mesh high-temperature resistant filter screen and cooled to room temperature to obtain a polymeric phosphorus-containing polyester plasticizer.

[0032] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 4 is that the mass ratio of adipic acid, sebacic acid, 1,4-butanediol, neopentyl glycol and 2-carboxyethylphenylphosphonic acid is 32:14:20:11:12, and the amount of tetrabutyl titanate is 0.05% of the total mass of the above five raw materials; the remaining steps are the same as those in Preparation Example 4.

[0033] Preparation Example 6 The difference between Preparation Example 6 and Preparation Example 4 is that the mass ratio of adipic acid, sebacic acid, 1,4-butanediol, neopentyl glycol, and 2-carboxyethylphenylphosphonic acid is 38:18:24:15:16, and the amount of tetrabutyl titanate is 0.12% of the total mass of the above five raw materials; the remaining steps are the same as those in Preparation Example 4.

[0034] Example

[0035] Example 1 Example 1 provides a method for preparing a low-smoke flame-retardant polyvinyl chloride composition, comprising the following steps: Preparation of flame retardant masterbatch: 14 kg of graded coating flame retardant and smoke suppressant synergist from Preparation Example 1, 1.5 kg of antimony trioxide, 1 kg of chlorinated paraffin-70, 5 kg of trioctyl trimellitate and 1.2 kg of polymeric phosphorus-containing polyester plasticizer from Preparation Example 4 were mixed and sand milled. Zirconia grinding beads with a diameter of 0.6 mm were used, the grinding bead filling rate was 70%, the slurry circulation flow rate was 350 L / h, the slurry was circulated and milled twice, the slurry temperature was 40℃, and the D90 particle size of the solid particles was 5-7 μm to obtain flame retardant masterbatch; Premix preparation: 100 kg of polyvinyl chloride resin, the remaining 20 kg of trioctyl trimellitate, 4.8 kg of polymeric phosphorus-containing polyester plasticizer from Preparation Example 4, 3 kg of calcium-zinc composite heat stabilizer, 0.5 kg of acrylate processing aid, and 0.2 kg of antioxidant were added to a high-speed mixer and mixed at 600 rpm for 3 min. The speed of the high-speed mixer was increased to 1000 rpm. When the temperature of the mixture reached 100°C, flame retardant masterbatch and 0.3 kg of lubricant were added. The mixture was continued to be mixed until it reached 120°C before being discharged to obtain the premix. Extrusion granulation: The premixed material is added to a twin-screw extruder for plasticization, extrusion, and granulation to obtain a low-smoke flame-retardant polyvinyl chloride composition. The twin-screw extruder is sequentially configured with a first plasticizing zone, a second plasticizing zone, a third plasticizing zone, a vacuum exhaust zone, and a metering zone along the material conveying direction. The temperature of the first plasticizing zone is 145℃, the temperature of the second plasticizing zone is 150℃, the temperature of the third plasticizing zone is 155℃, the temperature of the vacuum exhaust zone is 155℃, and the temperature of the metering zone is 158℃. The vacuum degree of the vacuum exhaust zone is -0.06MPa, the screw speed of the twin-screw extruder is 120rpm, and the residence time of the material in the twin-screw extruder is 4min.

[0036] Example 2 The difference between Example 2 and Example 1 is that the flame retardant masterbatch was prepared as follows: 19 kg of the graded coating flame retardant and smoke suppressant synergist from Example 1, 2.5 kg of antimony trioxide, 2.5 kg of chlorinated paraffin-70, 6.4 kg of trioctyl trimellitate, and 2.1 kg of the polymeric phosphorus-containing polyester plasticizer from Example 4 were mixed and milled. Zirconia grinding beads with a diameter of 0.6 mm were used, the grinding bead filling rate was 70%, the slurry circulation flow rate was 350 L / h, the slurry was circulated and milled twice, the slurry temperature was 40 °C, and the D90 particle size of the solid particles was 5-7 μm to obtain the flame retardant masterbatch. Premix preparation: 100 kg of polyvinyl chloride resin, the remaining 25.6 kg of trioctyl trimellitate, 8.4 kg of polymeric phosphorus-containing polyester plasticizer from Preparation Example 4, 4.5 kg of calcium-zinc composite heat stabilizer, 1.2 kg of acrylate processing aid, and 0.5 kg of antioxidant were added to a high-speed mixer and mixed at 600 rpm for 3 min. The speed of the high-speed mixer was increased to 1000 rpm. When the temperature of the mixture reached 100°C, flame retardant masterbatch and 0.45 kg of lubricant were added. Mixing was continued until the temperature reached 120°C before discharge to obtain the premix. The remaining steps were the same as in Example 1.

[0037] Example 3 The difference between Example 3 and Example 1 is that the flame retardant masterbatch was prepared as follows: 24 kg of the graded coating flame retardant and smoke suppressant synergist from Example 1, 3.5 kg of antimony trioxide, 4 kg of chlorinated paraffin-70, 8 kg of trioctyl trimellitate, and 3 kg of the polymeric phosphorus-containing polyester plasticizer from Example 4 were mixed and milled. Zirconia grinding beads with a diameter of 0.6 mm were used, the grinding bead filling rate was 70%, the slurry circulation flow rate was 350 L / h, the slurry was circulated and milled twice, the slurry temperature was 40 °C, and the D90 particle size of the solid particles was 5-7 μm to obtain the flame retardant masterbatch. Premix preparation: 100 kg of polyvinyl chloride resin, the remaining 32 kg of trioctyl trimellitate, 12 kg of polymeric phosphorus-containing polyester plasticizer from Preparation Example 4, 6 kg of calcium-zinc composite heat stabilizer, 2 kg of acrylate processing aids, and 0.8 kg of antioxidant were added to a high-speed mixer and mixed at 600 rpm for 3 min. The speed of the high-speed mixer was increased to 1000 rpm. When the temperature of the mixture reached 100°C, flame retardant masterbatch and 0.6 kg of lubricant were added. Mixing was continued until the temperature reached 120°C before discharge to obtain the premix. The remaining steps were the same as in Example 1.

[0038] Example 4 The difference between Example 4 and Example 2 is that the graded coating flame retardant and smoke suppressant synergist used in Example 2 is selected; the remaining steps are the same as in Example 2.

[0039] Example 5 The difference between Example 5 and Example 2 is that the graded coating flame retardant and smoke suppressant synergist is the same as that in Example 3; the remaining steps are the same as in Example 2.

[0040] Example 6 The difference between Example 6 and Example 2 is that the polymeric phosphorus-containing polyester plasticizers are all selected from the polymeric phosphorus-containing polyester plasticizers in Preparation Example 5; the remaining steps are the same as in Example 2.

[0041] Example 7 The difference between Example 7 and Example 2 is that the polymeric phosphorus-containing polyester plasticizers are all selected from the polymeric phosphorus-containing polyester plasticizers in Preparation Example 6; the remaining steps are the same as in Example 2.

[0042] Example 8 The difference between Example 8 and Example 2 lies in the preparation of the flame retardant masterbatch: 19 kg of the graded coating flame retardant and smoke suppressant synergist from Preparation Example 1, 2.5 kg of antimony trioxide, 2.5 kg of chlorinated paraffin-70, 6.4 kg of trioctyl trimellitate, 2.1 kg of the polymeric phosphorus-containing polyester plasticizer from Preparation Example 4, and 2.8 kg of piperazine pyrophosphate were mixed and milled using 0.6 mm diameter zirconia grinding beads with a filling rate of 70%. The slurry circulation flow rate was 350 L / h, and the grinding was repeated twice. The slurry temperature was 40 °C, and the grinding was continued until the D90 particle size of the solid particles was 5-7 μm, thus obtaining the flame retardant masterbatch. The remaining steps were the same as in Example 2.

[0043] Example 9 The difference between Example 9 and Example 2 lies in the preparation of the flame retardant masterbatch: 19 kg of the graded coating flame retardant and smoke suppressant synergist from Preparation Example 1, 2.5 kg of antimony trioxide, 2.5 kg of chlorinated paraffin-70, 6.4 kg of trioctyl trimellitate, 2.1 kg of the polymeric phosphorus-containing polyester plasticizer from Preparation Example 4, and 1.2 kg of melamine cyanurate were mixed and milled using 0.6 mm diameter zirconia grinding beads with a filling rate of 70%. The slurry circulation flow rate was 350 L / h, and the grinding was repeated twice. The slurry temperature was 40 °C, and the grinding was continued until the D90 particle size of the solid particles was 5–7 μm, thus obtaining the flame retardant masterbatch. The remaining steps were the same as in Example 2.

[0044] Example 10 The difference between Example 10 and Example 2 lies in the preparation of the flame retardant masterbatch: 19 kg of the graded coating flame retardant and smoke suppressant synergist from Preparation Example 1, 2.5 kg of antimony trioxide, 2.5 kg of chlorinated paraffin-70, 6.4 kg of trioctyl trimellitate, 2.1 kg of the polymeric phosphorus-containing polyester plasticizer from Preparation Example 4, 2.8 kg of piperazine pyrophosphate, and 1.2 kg of melamine cyanurate were mixed and milled using 0.6 mm diameter zirconia grinding beads with a filling rate of 70%. The slurry circulation flow rate was 350 L / h, and the grinding was repeated twice. The slurry temperature was 40 °C, and the grinding was continued until the D90 particle size of the solid particles was 5–7 μm, thus obtaining the flame retardant masterbatch. The remaining steps were the same as in Example 2.

[0045] Example 11 The difference between Example 11 and Example 10 lies in the preparation of the flame retardant masterbatch: 19 kg of the graded coating flame retardant and smoke suppressant synergist from Preparation Example 1, 2.5 kg of antimony trioxide, 2.5 kg of chlorinated paraffin-70, 6.4 kg of trioctyl trimellitate, 2.1 kg of the polymeric phosphorus-containing polyester plasticizer from Preparation Example 4, 2.8 kg of piperazine pyrophosphate, 1.2 kg of melamine cyanurate, and 0.9 kg of zinc molybdate were mixed and milled using 0.6 mm diameter zirconia grinding beads with a filling rate of 70%. The slurry circulation flow rate was 350 L / h, and the grinding was repeated twice. The slurry temperature was 40 °C, and the grinding was continued until the D90 particle size of the solid particles was 5–7 μm, thus obtaining the flame retardant masterbatch. The remaining steps were the same as in Example 10.

[0046] Example 12 The difference between Example 12 and Example 10 lies in the preparation of the flame retardant masterbatch: 19 kg of the graded coating flame retardant and smoke suppressant synergist from Preparation Example 1, 2.5 kg of antimony trioxide, 2.5 kg of chlorinated paraffin-70, 6.4 kg of trioctyl trimellitate, 2.1 kg of the polymeric phosphorus-containing polyester plasticizer from Preparation Example 4, 2.8 kg of piperazine pyrophosphate, 1.2 kg of melamine cyanurate, and 1.9 kg of boehmite were mixed and milled using 0.6 mm diameter zirconia grinding beads with a filling rate of 70%. The slurry circulation flow rate was 350 L / h, and the grinding was repeated twice. The slurry temperature was 40 °C, and the grinding was continued until the D90 particle size of the solid particles was 5–7 μm, thus obtaining the flame retardant masterbatch. The remaining steps were the same as in Example 10.

[0047] Example 13 The difference between Example 13 and Example 10 lies in the preparation of the flame retardant masterbatch: 19 kg of the graded coating flame retardant and smoke suppressant synergist from Preparation Example 1, 2.5 kg of antimony trioxide, 2.5 kg of chlorinated paraffin-70, 6.4 kg of trioctyl trimellitate, 2.1 kg of the polymeric phosphorus-containing polyester plasticizer from Preparation Example 4, 2.8 kg of piperazine pyrophosphate, 1.2 kg of melamine cyanurate, 0.9 kg of zinc molybdate, and 1.9 kg of boehmite were mixed and milled using 0.6 mm diameter zirconia grinding beads with a filling rate of 70%. The slurry circulation flow rate was 350 L / h, and the grinding was repeated twice. The slurry temperature was 40 °C, and the grinding was continued until the D90 particle size of the solid particles was 5–7 μm, thus obtaining the flame retardant masterbatch. The remaining steps were the same as in Example 10.

[0048] Example 14 The difference between Example 14 and Example 13 is that the extrusion granulation: the premixed material is added to a twin-screw extruder for plasticization, extrusion, and granulation to obtain a low-smoke flame-retardant polyvinyl chloride composition; wherein the twin-screw extruder is sequentially arranged with a first plasticizing zone, a second plasticizing zone, a third plasticizing zone, a vacuum exhaust zone, and a metering zone along the material conveying direction; the temperature of the first plasticizing zone is 147°C, the temperature of the second plasticizing zone is 152°C, the temperature of the third plasticizing zone is 157°C, the temperature of the vacuum exhaust zone is 158°C, and the temperature of the metering zone is 161°C; the vacuum degree of the vacuum exhaust zone is -0.07MPa, the screw speed of the twin-screw extruder is 185rpm, and the residence time of the material in the twin-screw extruder is 2.7min; the remaining steps are the same as in Example 13.

[0049] Example 15 The difference between Example 15 and Example 13 is in the extrusion granulation: the premixed material is added to a twin-screw extruder for plasticization, extrusion, and granulation to obtain a low-smoke flame-retardant polyvinyl chloride composition; wherein the twin-screw extruder is sequentially configured with a first plasticizing zone, a second plasticizing zone, a third plasticizing zone, a vacuum exhaust zone, and a metering zone along the material conveying direction; the temperature of the first plasticizing zone is 150°C, the temperature of the second plasticizing zone is 155°C, the temperature of the third plasticizing zone is 160°C, the temperature of the vacuum exhaust zone is 162°C, and the temperature of the metering zone is 165°C; the vacuum degree of the vacuum exhaust zone is -0.09MPa, the screw speed of the twin-screw extruder is 250rpm, and the residence time of the material in the twin-screw extruder is 1.5min; the remaining steps are the same as in Example 13.

[0050] Comparative Example

[0051] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the flame retardant masterbatch was prepared as follows: 8 kg of antimony trioxide, 5 kg of chlorinated paraffin-70 and 38 kg of trioctyl trimellitate were mixed and milled using zirconia grinding beads with a diameter of 0.6 mm, a grinding bead filling rate of 70%, a slurry circulation flow rate of 350 L / h, and the mixture was milled twice. The slurry temperature was 40 °C. The grinding was carried out until the D90 particle size of the solid particles was 5-7 μm, and the flame retardant masterbatch was obtained. Premix preparation: 100 kg of polyvinyl chloride resin, 4.5 kg of calcium-zinc composite heat stabilizer, 0.5 kg of acrylate processing aid and 0.2 kg of antioxidant were added to a high-speed mixer and mixed at 600 rpm for 3 min. The speed of the high-speed mixer was increased to 1000 rpm. When the temperature of the mixture reached 100°C, flame retardant masterbatch and 0.3 kg of lubricant were added. The mixture was continued to be mixed until it reached 120°C before being discharged to obtain the premix. The remaining steps were the same as in Example 1.

[0052] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the flame retardant masterbatch was prepared as follows: 15 kg of zinc hydroxystannate, 5 kg of zinc borate, and 38 kg of trioctyl trimellitate were mixed and milled using zirconia grinding beads with a diameter of 0.6 mm and a filling rate of 70%. The slurry circulation flow rate was 350 L / h, and the grinding was repeated twice. The slurry temperature was 40 °C. The grinding was carried out until the D90 particle size of the solid particles was 5-7 μm, thus obtaining the flame retardant masterbatch. Premix preparation: 100 kg of polyvinyl chloride resin, 4.5 kg of calcium-zinc composite heat stabilizer, 0.5 kg of acrylate processing aid and 0.2 kg of antioxidant were added to a high-speed mixer and mixed at 600 rpm for 3 min. The speed of the high-speed mixer was increased to 1000 rpm. When the temperature of the mixture reached 100°C, flame retardant masterbatch and 0.3 kg of lubricant were added. The mixture was continued to be mixed until it reached 120°C before being discharged to obtain the premix. The remaining steps were the same as in Example 1.

[0053] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the graded coating flame retardant and smoke suppressant synergist was replaced with a mixture obtained by directly physical mixing flake sericite, zinc hydroxystannate, zinc borate, zinc phytate and epoxy polysiloxane in a mass ratio of 14:50:30:5:3, and the replacement amount was the same; the remaining steps were the same as in Example 1.

[0054] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that antimony trioxide and chlorinated paraffin-70 are not added to the flame retardant masterbatch; the remaining steps are the same as in Example 1.

[0055] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that no polymeric phosphorus-containing polyester plasticizer was added to either the flame retardant masterbatch or the premix, and the amount of polymeric phosphorus-containing polyester plasticizer was made up with an equal mass of trioctyl trimellitate; the remaining steps were the same as in Example 1.

[0056] Application examples

[0057] Application Example 1 Application Example 1 provides a security cable.

[0058] A security cable includes a conductor, an insulation layer covering the outside of the conductor, and a sheath layer located outside the insulation layer, wherein the thickness of the sheath layer is 0.08 times the outer diameter of the security cable.

[0059] Application Example 1 also provides a method for manufacturing a security cable, comprising the following steps: Forty-eight T2 annealed soft round copper wires with a diameter of 0.20 mm were bundled together at a pitch of 30 mm to produce a product with a nominal cross-sectional area of ​​1.5 mm². 2The conductor is prepared by drying J-70 type 70℃ insulation grade soft polyvinyl chloride cable material at 70℃ for 2.5h and extruding it onto the outside of the conductor at 140-170℃ to form an insulation layer with a thickness of 0.8mm, thus obtaining an insulated core. Seven insulated cores are stranded together in a 1+6 arrangement with a pitch of 100mm to obtain a cable core. The low smoke flame retardant polyvinyl chloride composition in Example 1 is dried at 65℃ for 3h and extruded onto the outside of the cable core at 160-170℃ to form a sheath layer with a sheath layer thickness of 0.08 times the outer diameter of the security cable. After segmented water cooling, outer diameter detection, printing, and winding, the security cable is obtained.

[0060] Application Example 2-15 The difference between Application Example 2-15 and Application Example 1 is that the low-smoke flame-retardant polyvinyl chloride composition is selected differently, see Table 1.

[0061] Table 1 Selection of Low Smoke Flame Retardant Polyvinyl Chloride Compositions

[0062] Application Example 16 The difference between Application Example 16 and Application Example 14 is that the sheath thickness is 0.12 times the outer diameter of the security cable; the rest of the steps are the same as in Application Example 14.

[0063] Application Example 17 The difference between Application Example 17 and Application Example 14 is that the sheath thickness is 0.15 times the outer diameter of the security cable; the remaining steps are the same as in Application Example 14.

[0064] Comparative Application Examples

[0065] Comparative Application Example 1 The difference between Application Example 1 and Application Example 2 is that the low-smoke flame-retardant PVC composition used in Comparative Example 1 is the same as that in Application Example 1.

[0066] Comparative Application Example 2 The difference between Application Example 2 and Application Example 1 is that the low-smoke flame-retardant PVC composition used in Comparative Example 2 is the same as that in Application Example 1.

[0067] Comparative Application Example 3 The difference between Application Example 3 and Application Example 1 is that the low-smoke flame-retardant PVC composition used in Comparative Example 3 is the same as that in Application Example 1.

[0068] Comparative Application Example 4 The difference between Application Example 4 and Application Example 1 is that the low-smoke flame-retardant PVC composition used in Comparative Example 4 is the same as that in Application Example 1.

[0069] Comparative Application Example 5 The difference between Application Example 5 and Application Example 1 is that the low-smoke flame-retardant PVC composition used in Comparative Example 5 is the same as that in Application Example 1.

[0070] Performance testing experiment

[0071] Oxygen Index: Tested according to GB / T 2406.2-2009 "Determination of Combustion Behavior by Oxygen Index Method for Plastics - Part 2: Room Temperature Test". Samples were taken from the sheath layers of security cables obtained from various application examples and comparative application examples. The sheath material was hot-pressed at 165±2℃ into sheets with a thickness of 4.0±0.2mm, and cut into standard strip samples. The samples were conditioned for 88 hours at a temperature of 23±2℃ and a relative humidity of 50±5%. The samples were vertically mounted in the oxygen index meter, and the upper part of the sample was ignited in a mixed atmosphere of oxygen and nitrogen. The oxygen volume fraction was gradually adjusted until the lowest oxygen volume fraction required to sustain combustion for 180s was taken as the oxygen index. Five samples were tested in each group, and the average value was taken, with the result retained to 0.1%.

[0072] NBS: Testing was conducted according to GB / T 8323.2-2008 "Plastic Smoke Generation Part 2: Single Chamber Method for Determination of Smoke Density". Samples were taken from the sheath layers of security cables obtained from various application examples and comparative application examples. The sheath material was hot-pressed into 75mm×75mm×2.0mm specimens at 165±2℃ and conditioned for 48 hours at 23±2℃ and 50±5% relative humidity. The test was conducted in flame mode at a radiant heat flux of 25kW / m². The maximum specific optical density Ds,max within 20 minutes of the test was recorded and recorded as the NBS smoke density. Three specimens were tested in each group, and the average value was taken. The result was rounded to the nearest integer.

[0073] CBI: CBI is calculated using the formula (Oxygen Index / 32) × (200 / NBS), where the Oxygen Index and NBS are the average test values ​​of the same group of samples, and the calculation result is rounded to two decimal places. CBI is only used as an internal comprehensive indicator to evaluate the balance between flame retardant performance and smoke suppression performance, and does not replace the individual judgment of Oxygen Index and NBS; in this application, an Oxygen Index of not less than 32% and an NBS of not more than 200 are used as the basic conditions for achieving the expected flame retardant and smoke suppression performance simultaneously.

[0074] Bundled Combustion Performance: Testing was conducted according to GB / T 18380.33—2022 "Cables and Optical Cables - Combustion Tests under Flame Conditions - Part 33: Vertical Flame Spread Test for Vertically Installed Bundled Wires and Cables - Class A". Security cables obtained from Application Examples 14, 16, and 17 were used as samples. Each sample segment was 3.5 m long and placed in an environment of 20±10℃ for 16 h, keeping the samples dry. The volume of non-metallic material per meter of a single cable was measured, and the number of samples was determined based on the measurement results, ensuring that the total nominal volume of non-metallic material in all sample segments reached 7 L / m. The sample segments were vertically installed in front of a standard steel ladder and ignited for 40 min using a specified ribbon propane burner. After ignition was stopped, the sample flame was allowed to extinguish and cool. Soot was wiped off the sample surface, and the vertical distance from the bottom edge of the burner to the highest point of the charred or damaged portion of the sample was measured as the char height.

[0075] Overall cable smoke density: The test was conducted according to GB / T 17651.2—2021 "Determination of smoke density of cables or optical fibers under specific conditions - Part 2: Test procedures and requirements". Security cables from Application Examples 14, 16, and 17 were used. The number and length of samples were determined according to the standard specifications based on the cable's outer diameter. The samples were arranged horizontally in a smoke density test chamber and ignited under specified standard fire conditions. The transmittance inside the test chamber was continuously measured using light sources and photoelectric detection devices located on opposite sides of the chamber. The transmittance change over time was continuously recorded during the test, and the lowest transmittance measured throughout the entire test was taken as the overall cable smoke density test result. Each application example was tested twice in parallel. If the difference between the two results was no greater than 5 percentage points, the arithmetic mean of the two results was taken.

[0076] Table 2 Performance test results of the sheath layer

[0077] Table 3 Performance test results of security cables

[0078] Combining Application Example 1 and Comparative Application Examples 1-5, Comparative Application Example 1, using only a high-volume antimony trioxide and chlorinated paraffin-70 gas-phase flame retardant system, achieved an oxygen index of 33.0%, but a high NBS of 445, indicating that relying solely on antimony-chlorine gas-phase flame retardancy produces a large amount of smoke particles. Comparative Application Examples 2 and 4 had NBSs of 150 and 148, respectively, but oxygen indices of only 27.5% and 28.7%, indicating that while using only a condensed-phase smoke suppression system or omitting antimony trioxide and chlorinated paraffin-70 can reduce smoke density, it is difficult to meet flame retardant requirements. In Comparative Application Example 3, replacing the graded coating structure with a common mixture of components reduced the oxygen index to 31.0% and increased the NBS to 236, demonstrating that graded loading, zinc phytate coordination, and an epoxy-based polysiloxane protective layer can improve component dispersion and interfacial synergy. Compared to Application Example 5, which did not contain a polymeric phosphorus-containing polyester plasticizer, its oxygen index and smoke suppression performance were significantly reduced. This indicates that the plasticizer not only plays a plasticizing role but also serves as a continuous phosphorus and carbon source in the phosphorus-tin-zinc synergistic charring system. In contrast, Application Example 1 had an oxygen index of no less than 32% and NBS of no more than 200, demonstrating that the resulting sheath material can balance flame retardancy and smoke suppression performance.

[0079] Combined with Application Examples 1-3, Application Examples 2 and 3 have higher oxygen index and lower NBS compared to Application Example 1, indicating that appropriately increasing the amount of raw materials such as polymeric phosphorus-containing polyester plasticizer, graded coating flame retardant and smoke suppressant synergist, antimony trioxide and chlorinated paraffin-70 is beneficial to enhancing gas phase flame retardancy, condensed phase charring and inorganic barrier effects.

[0080] Combining Application Examples 2, 4, and 5, when Application Example 4 used the synergist obtained from Preparation Example 2, the oxygen index was 34.5% and the NBS was 187; when Application Example 5 used the synergist obtained from Preparation Example 3, the oxygen index increased to 36.6% and the NBS decreased to 165. This indicates that when preparing a graded coating type flame retardant and smoke suppressant synergist, the ratio of flake sericite, zinc hydroxystannate, zinc borate, zinc phytate, and epoxy polysiloxane is (10-18):(45-55):(25-35):(3-7):(2-4), which is beneficial for forming a continuous composite loading structure on the surface of flake sericite.

[0081] Combining Application Examples 2, 6, and 7, Application Examples 6 and 7 show that the polymeric phosphorus-containing polyester plasticizers with different compositions still maintain good overall performance, indicating that when preparing polymeric phosphorus-containing polyester plasticizers, it is feasible to limit the ratio of adipic acid, sebacic acid, 1,4-butanediol, neopentyl glycol, and 2-carboxyethylphenylphosphonic acid to (32-38):(14-18):(20-24):(11-15):(12-16).

[0082] Combining Application Examples 2 and 8-10, the addition of piperazine pyrophosphate or melamine cyanurate alone can improve the flame retardant and smoke suppressant performance on the basis of Application Example 2. However, the addition of both in Application Example 10 resulted in an oxygen index of 38.5%, a decrease in NBS to 143, and an increase in CBI to 1.68. These results indicate that the polymeric phosphorus-containing polyester plasticizer provides a carbon source and a partial phosphorus source, piperazine pyrophosphate provides an acid source, and melamine cyanurate provides a gas source. The three can form a carbon source-acid source-gas source synergistic expansion charring system, which further improves the flame retardant and smoke suppressant performance.

[0083] Combining Application Examples 10-13, it can be seen that adding zinc molybdate or boehmite alone to Application Example 10 can further reduce smoke density; Application Example 13, which adds both zinc molybdate and boehmite, has an oxygen index of 40.0%, an NBS of 113, and a CBI of 2.21, which is better than Application Examples 11 and 12. The reason is that zinc molybdate and zinc hydroxystannate in the graded coating flame retardant and smoke suppressant synergist form a molybdenum-tin-zinc polymetallic catalytic char formation and smoke suppression effect. The alumina phase formed by the heating of boehmite, the boron-containing phase formed by zinc borate, and the silicon-containing phase formed by epoxy polysiloxane jointly construct an aluminum-boron-silicon inorganic barrier. The chemical catalytic smoke suppression and physical barrier effects work together to make it more difficult for smoke precursors to enter the gas phase, further improving the flame retardant and smoke suppressant performance.

[0084] Combining Application Examples 13-15, Application Example 14 achieved the highest CBI, indicating that the preparation conditions in Example 14 were optimal when preparing low-smoke flame-retardant PVC compositions. The plasticizing temperature and shear strength were conducive to the uniform dispersion of each flame-retardant and smoke-suppressing component, while also reducing the thermal degradation of PVC.

[0085] Referring to Table 3, the bundled combustion charring heights of Application Examples 14, 16, and 17 were 1.06m, 0.88m, and 0.76m, respectively. It can be seen that as the ratio of sheath thickness to cable outer diameter increases from 0.08 to 0.15, the bundled combustion charring height gradually decreases, indicating that increasing the sheath thickness is beneficial for forming a thicker, continuous flame-retardant protective layer outside the cable core. Furthermore, the minimum light transmittance of the entire cable in Application Examples 14, 16, and 17 decreases sequentially. Although the increased sheath thickness slightly reduces the minimum light transmittance, the minimum light transmittance of Application Example 17 still reaches 80%, indicating that the hydroxyl tin in the graded coating type flame-retardant and smoke-suppressing synergist... Zinc phytate, zinc molybdate, and zinc molybdate in the formulation can promote the transformation of PVC pyrolysis products into the condensed phase; the inorganic barrier formed by zinc borate, flaky sericite, polysiloxane, and boehmite can also reduce the proportion of volatile smoke precursors migrating to the gas phase, thus allowing a thicker sheath to maintain high light transmittance; it can be seen that controlling the sheath thickness to 0.08-0.15 times the outer diameter of the security cable, a smaller sheath thickness is beneficial to reduce material usage and maintain high overall cable light transmittance; a larger sheath thickness can form a thicker and more continuous flame-retardant char layer, further reducing the flame spread height. Therefore, this thickness range allows security cables to have both good flame blocking ability and smoke suppression performance.

[0086] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A low-smoke flame-retardant polyvinyl chloride composition, characterized in that: The raw materials of the low-smoke flame-retardant polyvinyl chloride composition include the following components in parts by weight: 100 parts of polyvinyl chloride resin, 25-40 parts of trioctyl trimellitate, 6-15 parts of polymeric phosphorus-containing polyester plasticizer, 3-6 parts of calcium-zinc composite heat stabilizer, 14-24 parts of graded coating flame-retardant and smoke-suppressing synergist, 1.5-3.5 parts of antimony trioxide, 1-4 parts of chlorinated paraffin-70, 0.5-2 parts of acrylate processing aid, 0.3-0.6 parts of lubricant, and 0.2-0.8 parts of antioxidant; the graded coating flame-retardant and smoke-suppressing synergist includes a sheet-like sericite skeleton, a zinc hydroxystannate-zinc borate composite loading layer loaded on the surface of the sheet-like sericite skeleton, a zinc phytate coordination layer bonded to the surface of the zinc hydroxystannate-zinc borate composite loading layer, and an epoxy-based polysiloxane protective layer coating the outside of the zinc phytate coordination layer.

2. The low-smoke flame-retardant polyvinyl chloride composition according to claim 1, characterized in that: The preparation method of the graded coating type flame retardant and smoke suppressant synergist includes the following steps: Preparation of primary coating slurry: Flake sericite is added to a mixed dispersion medium of water and ethanol and dispersed at 800-1500 rpm for 20-40 min to obtain a flake sericite dispersion; zinc hydroxystannate and zinc borate are added to the flake sericite dispersion and sheared and dispersed at 1200-2000 rpm for 30-60 min, followed by wet milling to load the zinc hydroxystannate and zinc borate onto the surface of the flake sericite, forming a zinc hydroxystannate-zinc borate composite loading layer, thus obtaining a primary coating slurry; Preparation of secondary coating slurry: Zinc phytate is added to the primary coating slurry, the pH value of the system is adjusted to 5.5-7.0, and the mixture is stirred at 50-70℃ for 0.5-2 hours, so that the zinc phytate is bonded to the surface of the zinc hydroxystannate-zinc borate composite loading layer through coordination and hydrogen bonding to form a zinc phytate coordination layer, thus obtaining the secondary coating slurry; Preparation of epoxy polysiloxane protective layer: Epoxy polysiloxane is added to the secondary coating slurry and stirred at 70-90°C for 1-3 hours to coat the outer side of the zinc phytate coordination layer with epoxy polysiloxane, forming an epoxy polysiloxane protective layer; after filtration, washing, drying and pulverizing, a graded coating type flame retardant and smoke suppressant synergist is obtained; wherein the mass ratio of flaky sericite, zinc hydroxystannate, zinc borate, zinc phytate and epoxy polysiloxane is (10-18):(45-55):(25-35):(3-7):(2-4).

3. The low-smoke flame-retardant polyvinyl chloride composition according to claim 1, characterized in that: The preparation method of the polymeric phosphorus-containing polyester plasticizer includes the following steps: Esterification reaction: Adipic acid, sebacic acid, 1,4-butanediol, neopentyl glycol and 2-carboxyethylphenylphosphonic acid are mixed, tetrabutyl titanate is added, and the mixture is heated to 150-180℃ under nitrogen protection to carry out the esterification reaction until the acid value of the reaction system is reduced to below 15mgKOH / g. Polycondensation reaction: The reactants obtained from the esterification reaction step are heated to 190-220°C, and the absolute pressure of the reaction system is reduced to 0.5-5 kPa, and the polycondensation reaction is carried out for 1-4 hours; End-capping reaction: 2-ethylhexanol is added to the polycondensation product obtained in the polycondensation reaction step for end-capping reaction. The amount of 2-ethylhexanol is 1-5% of the mass of the obtained polycondensation product. The reaction is carried out at 170-200℃ for 0.5-2h to obtain the polymeric phosphorus-containing polyester plasticizer. The mass ratio of adipic acid, sebacic acid, 1,4-butanediol, neopentyl glycol and 2-carboxyethylphenylphosphonic acid is (32-38):(14-18):(20-24):(11-15):(12-16). The amount of tetrabutyl titanate is 0.05-0.12% of the total mass of the five raw materials.

4. The low-smoke flame-retardant polyvinyl chloride composition according to claim 1, characterized in that: The raw materials of the low-smoke flame-retardant polyvinyl chloride composition also include 1.5 to 4 parts by weight of piperazine pyrophosphate and 0.5 to 2 parts by weight of melamine cyanurate.

5. The low-smoke flame-retardant polyvinyl chloride composition according to claim 4, characterized in that: The raw materials of the low-smoke flame-retardant polyvinyl chloride composition also include 0.4 to 1.5 parts by weight of zinc molybdate and 0.8 to 3 parts by weight of boehmite.

6. A method for preparing a low-smoke flame-retardant polyvinyl chloride composition as described in any one of claims 1-5, characterized in that: Includes the following steps: Preparation of flame retardant masterbatch: The graded coating flame retardant and smoke suppressant synergist, antimony trioxide, chlorinated paraffin-70, part of trioctyl trimellitate and part of polymeric phosphorus-containing polyester plasticizer are mixed and milled to obtain flame retardant masterbatch. Premix preparation: Polyvinyl chloride resin, remaining trioctyl trimellitate, polymeric phosphorus-containing polyester plasticizer, calcium-zinc composite heat stabilizer, acrylate processing aids and antioxidants are added to a high-speed mixer and mixed. When the temperature of the mixture reaches 90-110℃, flame retardant masterbatch and lubricant are added. Mixing is continued until 115-125℃ before discharge to obtain the premix. Extrusion granulation: The premixed material is added to a twin-screw extruder and plasticized, extruded and granulated at 145-165°C to obtain a low-smoke flame-retardant polyvinyl chloride composition.

7. The method for preparing a low-smoke flame-retardant polyvinyl chloride composition according to claim 6, characterized in that: When the raw materials of the low-smoke flame-retardant polyvinyl chloride composition further include piperazine pyrophosphate, melamine cyanurate, zinc molybdate, and boehmite, the preparation steps of the flame-retardant masterbatch are as follows: mixing and milling the graded coating flame-retardant and smoke-suppressing synergist, antimony trioxide, chlorinated paraffin-70, a portion of trioctyl trimellitate, a portion of polymeric phosphorus-containing polyester plasticizer, piperazine pyrophosphate, melamine cyanurate, zinc molybdate, and boehmite to obtain the flame-retardant masterbatch.

8. The method for preparing a low-smoke flame-retardant polyvinyl chloride composition according to claim 6, characterized in that: In the extrusion granulation step, the twin-screw extruder is sequentially configured with a first plasticizing zone, a second plasticizing zone, a third plasticizing zone, a vacuum exhaust zone, and a metering zone along the material conveying direction. The temperature of the first plasticizing zone is 145–150°C, the temperature of the second plasticizing zone is 150–155°C, the temperature of the third plasticizing zone is 155–160°C, the temperature of the vacuum exhaust zone is 155–162°C, and the temperature of the metering zone is 158–165°C. The vacuum degree of the vacuum exhaust zone is -0.06 to -0.09 MPa. The screw speed of the twin-screw extruder is 120–250 rpm, and the residence time of the material in the twin-screw extruder is 1.5–4 min.

9. A security cable, characterized in that: It includes a conductor, an insulating layer covering the outside of the conductor, and a sheath layer located outside the insulating layer; the sheath layer is made of the low-smoke flame-retardant polyvinyl chloride composition according to any one of claims 1-5.

10. A security cable according to claim 9, characterized in that: The thickness of the sheath layer is 0.08-0.15 times the outer diameter of the security cable.